Measuring the share of imports in final consumption - Emmanuel Dhyne; Ayumu Ken Kikkawa; Magne Mogstad; Felix Tintelnot (National Bank of Belgium, 2023)
We use Belgian data on domestic firm-to-firm transactions and ask how the measurement of the share of imports in final consumption is affected when one uses data recorded at higher levels of aggregation. We find that aggregating detailed firm-to-firm transaction data to the firm level and imposing homogeneity assumptions in the composition of firms' input and output do not substantially affect the measurement of the share of imports in final consumption. However, using the national IO tables alone may understate the share of imports in final consumption and, thereby, the gains from trade.
Keywords: F10; F14; 330; Import content; firm-to-firm linkages; sectoral linkages